PENERAPAN DESAIN 4D PADA PENGEMBANGAN BUKU AJAR LOGIKA BERHITUNG MELALUI ANALISIS BERPIKIR SISWA SD - Lina Wijayanti (Program Studi Pendidikan Guru Sekolah Dasar STKIP Al Hikmah Surabaya, 2019)
This development research aims to be able to produce textbooks using 4D models for prospective elementary teacher students by emphasizing the results of analysis of elementary students' thinking and character education based. In addition, this study aims to determine the appropriateness of numerical logic textbooks through analysis of elementary school students' thinking. The development model used was adapted from the 4D development model with four stages namely define, design, develop, and disseminate. Data collection and analysis techniques used are documentation to obtain data related to textbooks, observations in analyzing the thinking flow of elementary school students and also during trials, as well as the results of validation from material and language experts. The results of the development showed that the feasibility of material and language obtained an average score of 3.88 with the Good category so that the textbook was declared valid and could be used in lectures. While the limited trial results obtained an average score of 4.3 in the category of very practice and in the final trial the average score of 4.2 obtained in the category of very practice.